RUSSIA-CHINA-CENTRAL ASIA: TRIVING FOR A NEW QUALITY IN INTERNATIONAL RELATIONS - KOMISSINA, Irina; KURTOV, Azhdar (CENTRAL ASIA AND THE CAUCASUS, 2004)
Human civilization has reached the point where it recognizes the need to build international relations on the humanistic principles set forth in international law. One of these principles is the inviolability of state borders. Respecting this principle is obligatory for maintaining peace, but this does not mean that territorial questions must be absolutely static and cannot evolve. Since the end of the Cold War, the current threats to security have shifted from ideological and military-strategic confrontation to the emergence of local conflicts and are largely related to the aggravation of old territorial disputes, inter-confession-al and ethnic differences, the use of natural resources, and so on. For example, according to the data published in the third edition of a book called “Border and Territorial Disputes,”1 there are 20 conflicts in Africa, 19 in Europe, 17 in Eastern Asia, 15 in America, and 12 in the Middle East. The claims of various countries to certain sectors of the Antarctic are seen as one territorial problem. As for Europe, it recently underwent a boom of border conflicts after the disintegration of Yugoslavia and the Soviet Union, the repercussions of which are still being felt today.